Electrical power submeter for quality and energy monitoring using Wemos microcontroller - Supriyono, Heru; Hogantara, Azra Reza Satria; Budiman, Aris (Institute of Advanced Engineering and Science, 2025)
Voltage, current, and frequency are three electrical energy variables that need to be monitored because if they do not comply with established standards, they can cause damage to electronic devices that use electrical energy. The objective of this article is to develop a submeter that can be used for monitoring both energy consumption and three power quality variables. The system was developed by using commercially available instruments involving the PZEM 004t sensor, the Wemos D1 mini microcontroller, and the Blynk platform on the smartphone. The use of the Blynk platform enables the system to log the monitored variables continuously in the form of a spreadsheet file and send them via email in order to be downloaded and used for further analysis. The results of calibration tests carried out using varying loads showed that the developed system has voltage measurement results with a difference of 1.35% when compared to measurement results using a commercial multimeter, while the difference for current measurements is 0.85%.